PET findings and neuropsychological deficits in a case of Fahr's disease - Hempel, Albrecht; Henze, Marcus; Berghoff, Christopher; García Caraballo, Nohazarahit María; Ody, Reinhard; Schröder, Johannes (Psychiatry research, 2001)
In a case of Fahr's disease with frontal lobe type dementia and hyperkinetic-hypotone syndrome, functional changes were investigated using positron emission tomography (PET) with 18F-fluorodeoxyglucose (FDG) as a tracer. Computed tomography showed bilateral calcifications in the putamen and globus pallidus consistent with the diagnosis of Fahr's disease and a frontally pronounced brain atrophy. In contrast, reduced glucose uptake in PET was not only confined to the areas mentioned above, but extended to the temporal and parietal cortices, bilaterally. These functional changes corresponded to the neuropsychological deficits observed, i.e. disturbed selective attention and cognitive flexibility, verbal perseverations, and declarative memory deficits. It is suggested that functional changes may precede cerebral atrophy in Fahr's disease and may reflect deficits in functional circuits, which involve both the basal ganglia and the frontal, parietal, and temporal lobes.